Avaliação das condições físicas das passagens em nível de trechos ferroviários da ilha de São Luís - Penha, Flávio Antonio Costa (2017)
The grade crossings are the crossings of two modes of transport, road and rail, although accidents are infrequent when compared to another type of road junction, the severity indices are high. This study offers through field data analysis, verification of the physical conditions of grade crossings, a case study that was carried out through the research in standards and after this stage, the inspections were carried out in loco. In this context, the objective of the present work is to evaluate the physical conditions of the Transnordestina Logística SA (FTL) grade crossings of a certain urban stretch of the city of São Luís-MA, pointing out possible risks to the safety and operation of railway vehicles and road tests and to analyze if these are in accordance with the main standards: ABNT NBR 15680: 2009 (grade crossings - project requirement) and ABNT NBR 15942: 2011 (protection equipment). The physical improvements are performed to provide safe conditions at grade crossings and the evaluation of road crossings are indispensable steps for the solution of the same